Development of the method for structural-parametric optimization in order to improve the efficiency of transition processes in periodic systems - Semenyshyna, Iryna; Haibura, Yuliia; Mushenyk, Iryna; Sklyarenko, Inna; Kononets, Vita (Eastern-European Journal of Enterprise Technologies, 2018)
In order to get the most out of the enterprise’s operational processes, the operational processes of functional systems are optimized. However, in the process of optimization, controlled systems over a significant amount of time operate under sub-optimal modes. In addition, changes in external conditions, quality parameters of raw materials, or cost estimates of the input and output products in a system operation, necessitate the repeated optimization process. It is not uncommon that the duration of the optimization process is comparable in terms of time, or even exceeds, the system operation time. That means that it is required to optimize the transition process itself. Currently, intensive research is conducted mainly into the development of a systematically substantiated multidisciplinary optimization criterion, and into search for methods of optimal control. Studies that investigate methods for improving the effectiveness of a transition process are carried out mainly by mathematicians, within the framework of the problem on the advanced search for an extremum. Accordingly, the well-known methods could be applied to improve the efficiency of a transition process through parametric optimization. By using the periodic system of proportional heating of a liquid, we considered the task on improving the effectiveness of the transition process by applying the method of structural-parametric optimization. We employ, as the optimization criterion, an estimated indicator, which was tested for its use as a formula of efficiency. The results of a comparative study into the reference technological process of a standard and a modified functional system have shown that the time required to enter the region close to optimal decreased by almost twice. In addition, the application of the new architecture for the functional system makes it possible to improve its reliability and service efficiency.